1999
DOI: 10.1515/joc.1999.20.3.110
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Commonly-used Trial Functions in the Variational Analysis of Ti:LiNbO3 Channel Waveguides

Abstract: Two common trial functions used in the variational method to solve the waveguiding modes of Ti:LiNbO 3 channel waveguides are compared in this paper. The first one has four parameters and the other has just two. The respective modal-field profiles described by them, as well as the respective fiber-to-waveguide coupling efficiencies estimated by these models, are rather different. We propose a self-consistent concept to examine the qualities of the trial fields and then show that the two-parameter model is bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…And the mode parameters are sought by the SOS algorithm [10][11][12]. The authors had shown that it is an efficient tool of optimizing the multivariable functions and solving the variational equations.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And the mode parameters are sought by the SOS algorithm [10][11][12]. The authors had shown that it is an efficient tool of optimizing the multivariable functions and solving the variational equations.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We had proposed a comprehensible self-consistent concept to do with it [12]. The concept and its usage are briefly described as follows.…”
Section: J-t>oj~-00mentioning
confidence: 99%
See 1 more Smart Citation